2017
DOI: 10.1007/s11250-017-1254-3
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants infection in domestic ruminants in Sudan

Abstract: The existence of peste des petits ruminants (PPR) in domestic ruminants and camels in Sudan during 2008-2012 was investigated. Lung tissues and serum samples were randomly collected from sheep, goats, cattle, and camels at different areas of Sudan. A total of 12,384 serum samples were collected from clinically healthy 7413 sheep, 1988 camels, 1501 cattle, 1459 goats, and 23 gazelles at different areas in the Sudan. They were examined for PPR antibodies using competitive ELISA (cELISA). The overall detected ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 26 publications
1
36
3
Order By: Relevance
“…Furthermore, multiple disease outbreaks and fatalities in camels associated with PPRV-infection with lineages LII, LIII [15], and LIV strains [12,16,17] have suggested PPR is an emerging disease in camels [12,[15][16][17]. However, clinical and virological results of field and experimental studies of PPRV-infection in camels and cattle are contradictory [11,14,17,[52][53][54]. There is no scientifically sound evidence that cattle or camelids may transmit the disease to other susceptible animals and act as reservoir hosts for PPRV to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multiple disease outbreaks and fatalities in camels associated with PPRV-infection with lineages LII, LIII [15], and LIV strains [12,16,17] have suggested PPR is an emerging disease in camels [12,[15][16][17]. However, clinical and virological results of field and experimental studies of PPRV-infection in camels and cattle are contradictory [11,14,17,[52][53][54]. There is no scientifically sound evidence that cattle or camelids may transmit the disease to other susceptible animals and act as reservoir hosts for PPRV to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sheep subclinically infected with PPRV are a known possible source of silent PPRV-spread [5,9]. PPRV RNA, antigen or infectious virus was detected in blood or tissue samples from different wild animal species [5,10], camels [11,12], buffaloes [13], and cattle [14], but no transmission to susceptible contact animals or shedding of infectious virus has so far been reported in any sound study for these Artiodactyla species. Additionally, due to multiple disease outbreaks in camels, which were associated with PPRV-infection with any of the lineages LII, LIII [15], or LIV, PPR has been discussed an emerging disease in camels [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is not unexpected because PPR is endemic in the country and viral genome and antibody-based prevalence has previously been reported in wild animals (Ibex), semi-domestic yak (Abubakar et al, 2019) and small ruminants Zahur et al, 2008;Zahur et al, 2011;Abubakar et al, 2011). The virus generally causes infection in small ruminants worldwide (Al-Majali et al, 2008;Megersa et al, 2011;Intisar et al, 2017); however, it also has the propensity to cause infection in wild ungulates (Aziz-ul-Rahman et al, 2018, Rahman, 2019 and other unusual hosts such as buffalo, cattle (Balamurugan et al, 2014) and camels (Omani et al, 2019). Indeed, there exists a controversy regarding clinical infection of PPRV in camels (Ul-Rahman et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…While investigating the prevalence of PPR in camels in different areas of Sudan, PPRV antigen was detected in 45.1% (214/474) of the tested pneumonic lung specimens of clinically healthy camels using immunocapture ELISA (11). Further investigation on PPR in domestic ruminants of Sudan from 2008 to 2012 showed that PPR antigen was detected in 33.6% of the lung tissue samples of camels (n = 1,276), which was higher than that in goats (21.1%), sheep (15.4%), and cattle (12.3%) (14). A number of studies have also been FIGURE 2 | The Bayesian Phylogenetic tree was constructed based on Morbillivirus Hemagglutinin and its receptors SLAM and Nectin-4 gene.…”
Section: Pprv Infection In Camelidsmentioning
confidence: 89%
“…On the other hand, white-tail deer challenged with PPRV exhibited clinical signs similar to those in goat (29). Abundant reports of natural infection of PPR disease in gazelles, ibexes, bharals, wild goats (Capra aegagrus), wild sheep (Ovis orientalis) have also been documented (7,14,20,22,23,26,31). Additionally, Barbary sheep (Ammotragus lervia) and Afghan Markhor goat (Capra falconeri) died from PPRV infection, which belongs to lineage IV (21).…”
Section: Ppr Infection In Typical Host or Small Ruminantsmentioning
confidence: 91%